The Basic Four Approach to Clinical Neuroscience Instruction: Using Cognitive Load Theory to Enhance Case-based Learning. (December 2018) - Sunde, Kiri E; Cutsforth-Gregory, Jeremy K; Leep Hunderfund, Andrea N
Among medical students, neurosceince is considered a notoriously difficult subject. This challenges faculty to teach preclinical neurology in more engaging, efficient, and prioritized ways. Traditional approaches to neuroscience instruction typically begin with neuroanatomy and advance to clinical problem solving after this foundation of knowledge is in place. Over the past 45 years, neurology faculty at Mayo Clinic Alix School of Medicine have developed and iteratively refined an inverted approach called The Basic Four. The Basic Four uses authentic clinical scenarios as the basis for neuroscience instruction and incorporates principles from cognitive load theory to calibrate load on students' working memory. This perspective describes The Basic Four and illustrates how cognitive load theory can be used to enhance case-based learning.